ANALISIS KESALAHAN PENUNJUKAN INDIKATOR TEKANAN BAHAN BAKAR DITINJAU DARI KERUSAKAN TRANSDUCER PADA PESAWAT SOCATA TB-10 DI SEKOLAH TINGGI PENERBANGAN INDONESIA CURUG-TANGERANG - Bela Firmantoyo; Sihono (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
Trainer aircraft type Socata TB-10 is one of the types of aircraft piston engine (engine) used by Indonesian Civil Aviation Institute. The aircraft began to be used for flight training for cadets STPI Airmen Department since August 1997. During operation of the Socata TB-10 aircraft within a certain time there is a mistake appointing fuel pressure indicator on all Socata TB-10 aircraft that existed at Indonesian Civil Aviation Institute Curug-Tangerang. This designation errors either low pressure, high pressure in the run-up both positions, climbing cruising and landing. To support error analysis designation fuel pressure indicator required some theories that the aircraft fuel system TB-10, the designation system fuel pressure, transducer, transducer sensitivity. To solve these problems required transducer calibration test of the fuel components. Testing was conducted at the Indonesian Institute of Sciences Research Center Instrumentation Calibration and Metrology (KIM-LIPI). Based transducer calibration test and results analysis is, the cause of the error designation fuel pressure indicator in terms of damage to the fuel pressure transducer is rated third transducer sensitivity tested had a sensitivity value greater than the allowed value sensitivity (standard). Resulting voltage change corresponding outgoing errors resulting in the appointment of a fuel pressure indicator on the Socata TB-10 aircraft owned by Indonesian Civil Aviation Institute Curug-Tangerang.